CAR-T cells: prospective genetic engineering approach to orchestrate solid tumor in lung cancer - Angeline Felisca Tanujaya; Dhea Anggraini; Ahmad Dzulfikri Nurhan (Research Results in Pharmacology)
Introduction: Various strategies, starting with surgery, systemic radiation therapy with cytotoxic chemotherapy, and immunotherapy, have been carried out to address mortality from lung cancer. None of these therapies has showed remarkably successful treatments for lung cancer. Developing technology leads to innovation of cancer-targeted therapy as an ideal strategy. Chimeric antigen receptor T cells (CAR-T cells) are one of the novel immunotherapy approaches in genetic engineering. CAR-T therapy has showed promising results as the cancer-targeted therapy.